Formulation of mixed food ingredients with mackerel fish flour (Rastrelliger neglectus) and tempe flour substitution for complementary foods incidence stunting under five years old - Permatasari, Oktavina; Tunjung, Andrea Putri Sekar; Ismawanti, Zuhria (Alma Ata University Press, 2026)
ABSTRAK Latar Belakang: Permasalahan gizi Indonesia yang belum teratasi pada kelompok balita yaitu stunting. Riskesdas Tahun 2018 stunting di Jawa Tengah pada baduta 33,3%, Tahun 2021 Kota Semarang 3,10%. Stunting balita dapat terjadi karena kurang asupan zat gizi. Upaya penanganan stunting Kota Semarang diperlukan peningkatan kandungan gizi MP-ASI dengan substitusi bahan pangan tinggi protein dan zat gizi mikro. Tujuan: Memperoleh formulasi BMC bubur instan substitusi ikan kembung dan tepung tempe yang diterima balita dengan menentukan nilai gizi dan anjuran takaran saji konsumsi. Metode: Penelitian kuantitatif dengan metode eksperimen, Rancangan Acak Lengkap. Objek yang diteliti BMC bubur instan dengan 3 kelompok perlakuan substitusi tepung tempe dan tepung ikan kembung sebagai pengganti beras merah, BMC F2 masing-masing 4%, F3 10%, F4 16%, serta F1 sebagai kontrol. Hasil: BMC bubur instan F3 (substitusi tepung ikan kembung 5% dan tepung tempe 5%) paling diterima panelis dengan energi 439,95 kkal, protein 14,67 g/100g, karbohidrat 60,69 g/100g, lemak 15,39 g/100g, serat 25,66 g/100g, vitamin A 14,56 µ/100g, vitamin C 226,5 mg/100g, zat besi 0,29 mg/100g, zink 19,27 mg/100g, kelarutan sesuai standar, densitas kamba lebih baik dari bubur instan komersial, lolos uji cemaran mikrobiologi berdasarkan standar SNI Kesimpulan: BMC bubur instan substitusi tepung ikan kembung dan tepung tempe layak dikonsumsi dan digunakan sebagai MP-ASI makanan utama balita stunting dengan takaran saji 20 gram berat kering atau 60 gram rehidrasi memenuhi 395,93 kkal energi, serta 100% protein, karbohidrat, lemak, serat, vitamin C, dan zink. ABSTRACT Background : Stunting is a persistent nutritional problem in Indonesia affecting toddlers. The 2018 Basic Health Research showed stunting cases in Central Java among toddlers at 33.3%, while in Semarang City in 2021 reached 3.10%. Stunting in toddlers can occur due to inadequate nutritional intake, particularly during complementary foods. In an effort to reduce stunting, it is necessary to increase the nutritional content of complementary foods substituting ingredients high protein and micronutrients. Objectives: Formulating instant porridge with substitutions of mackerel and tempeh flour that accepted by toddlers while ensuring appropriate nutritional content and recommended serving sizes. Methods: This research using a quantitative experimental approach with a Completely Randomized Design (CRD). The study focused on BMC instant porridge, including three treatment groups with substitutions of tempeh and mackerel flour, BMC F2 4%, F3 10%, F4 16%, F1 as a control. Results: BMC instant porridge formula 3 was the preferred by panelists. This formulation provides 439.95 kcal of energy, 14.67 g/100g protein, 60.69 g/100g carbohydrates, 15.39 g/100g fat, 25.66 g/100g fiber, 14.56 µg/100g vitamin A, 226.5 mg/100g vitamin C, 0.29 mg/100g iron, and 19.27 mg/100g zinc. Meets solubility standards, has a density superior to commercial instant porridge, and passes microbiological contamination tests. Conclusions: BMC instant porridge substituted with mackerel and tempeh flour, is suitable as complementary food for stunted toddlers. Each serving, consisting of 20 grams of dry porridge or 60 grams when rehydrated, provides 395.93 kcal of energy,100% of the recommended intake for protein, carbohydrates, fat, fiber, vitamin C, and zinc.